Stability analysis and performance of promising sugarcane varieties for yield and quality traits - F.F.B. Abu-Ellail1*, A.B.A. El-Taib2and Y. A.M. Hefny3 (Indian Society of Plant Breeders, 2021)
Four promising varieties of sugarcane, along with the commercial variety, GT54/9 were evaluated for yield, yield components, and quality traits. The environments were different ages of harvest time (11, 12, and 13 months old) of two plant cane crops (2-years) at El-Mattana Agriculture Research Station farm during (2018-2019 and 2019-2020 seasons). The stability analysis of studied traits was performed. The results indicated that the promising varieties, environments, and their interaction had a highly significant effect on all studied traits in both the seasons except the age at the harvest time on purity in both seasons, the effect of the interaction on sucrose as well as a pol in second season only and on fiber in the first season only. It is obvious from the results that none of the tested varieties was superior to GT 54/9 for cane and sugar yield and stable implying the necessity of widening the genetic base to produce improved promising varieties. The stability analysis showed that GT 54/9 variety was stable for stalk height, stalk diameter, brix, reducing sugar, and fiber and recorded the highest cane yield and sugar yield. G2003/49 was stable for cane yield, sugar yield, brix, pol, and fiber. It ranked third in cane yield and the second sugar yield. The variety G2003/47 was stable for stalk diameter, sucrose, sugar recovery, and fiber and ranked fourth for cane yield and the third rank for sugar yield. G2004/26 was stable for stalk diameter, cane yield, reducing sugar, and fiber. It occupied the second and third ranks for cane yield and sugar yield respectively. G84/47 variety was stable for cane yield, sugar yield, brix, sucrose and fiber and ranked last for cane and sugar yield.